OPTIMIZATION OF DICLOFENAC POTASSIUM TRANSDERMAL PATCH FORMULA USING A COMBINATION OF POLYVYNIL PYRROLIDONE K 30, ETHYL CELLULOSE AND MENTHOL WITH SIMPLEX LATTICE DESIGN METHOD - Gunawan, Sahrul; Supriyadi, Supriyadi; Kuncahyo, Ilham (Universitas Muhammadiyah Magelang, 2024)
Diclofenac potassium is one of the NSAID drugs which can cause gastrointestinal irritation and damage to the small intestinal mucosa including erosion and ulceration. The purpose of this study was to determine the effect of the combination of PVP K 30, ethyl cellulose and menthol on organoleptic, thickness, weight uniformity, moisture and folding resistance of diclofenac potassium transdermal patch.This research is an experimental study that includes an experiment to optimize the formulation of a transdermal patch preparation with the active ingredient potassium diclofenac and a combination of PVP K 30, ethyl cellulose and menthol. The optimization method uses the simplex lattice design method. There are 13 formula designs consisting of a combination of PVP K 30, ethyl cellulose and menthol. Each formula was tested for organoleptic, thickness, weight uniformity, moisture and folding resistance. Then the optimum formula was determined and analyzed using the simplex lattice design method. The combination of PVP K 30, ethyl cellulose and menthol with a simplex lattice design has an effect on the transdermal patch of diclofenac potassium which increases the consistency of the patch surface, reduces the thickness directly proportional to the weight of the patch and increases folding resistance. The proportion of PVP K 30, ethyl cellulose and menthol that can produce the optimum formula for diclofenac potassium transdermal patches with the simplex lattice design on the critical parameters of thickness, moisture, folding resistance and penetration tests, namely PVP K 30 of 14.87%, ethyl cellulose of 10.00% and 5.13% menthol.